Broad Bandwidth, Self‐Powered Acoustic Sensor Created by Dynamic Near‐Field Electrospinning of Suspended, Transparent Piezoelectric Nanofiber Mesh. Issue 28 (8th June 2020) - Wang, Wenyu; Stipp, Patrick N.; Ouaras, Karim; Fathi, Saeed; Huang, Yan Yan Shery
Abstract: Freely suspended nanofibers, such as spider silk, harnessing their small diameter (sub‐micrometer) and spanning fiber morphology, behave as a nonresonating acoustic sensor. The associated sensing characteristics, departing from conventional resonant acoustic sensors, could be of tremendous interest for the development of high sensitivity, broadband audible sensors for applications in environmental monitoring, biomedical diagnostics, and internet‐of‐things. Herein, a low packing density, freely suspended nanofiber mesh with a piezoelectric active polymer is fabricated, demonstrating a self‐powered acoustic sensing platform with broad sensitivity bandwidth covering 200–5000 Hz at hearing‐safe sound pressure levels. Dynamic near‐field electrospinning is developed to fabricate in situ poled poly(vinylidene fluoride‐ co ‐trifluoroethylene) (P(VDF‐TrFE)) nanofiber mesh (average fiber diameter ≈307 nm), exhibiting visible light transparency greater than 97%. With the ability to span the nanomesh across a suspension distance of 3 mm with minimized fiber stacking (≈18% fiber packing density), individual nanofibers can freely imitate the acoustic‐driven fluctuation of airflow in a collective manner, where piezoelectricity is harvested at two‐terminal electrodes for direct signal collection. Applications of the nanofiber mesh in music recording with good signal fidelity are demonstrated. Abstract : A broad bandwidth acoustic sensor, inspired by the acoustic sensing mechanism of spider silk, is fabricated by an original dynamic near‐field electrospinning method. Composed of freely suspended piezoelectric nanofibers, the transparent acoustic sensor has high sensitivity throughout the majority of the audible sound spectrum at hearing‐safe loudness level.